Quality of life in patients with chronic obstructive pulmonary disease at Pulmonary Community Health Centre Makassar - Irianti, Elva Cristy; A. A., Arsunan; Tahir Abdullah, M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Chronic obstructive pulmonary disease (COPD) that causes damage to lung conditions such as dyspnea that affects to social and psychological life of the sufferer which overall affects the quality of life. This reaserch aims to focuses on factors related to the quality of life patients with COPD at the Pulmonary Community Health Center, Makassar. Methods: This study used cross sectional study design. Population in this research were patients with COPD who undergo treatment period of October-December 2017 that was as much as 381. Sampling was done by consecutive sampling with total sampel 160 responden. Data analysis consisted of univariate, bivariate with chi square test and multivariate analysis with logistic regression. Results: The results showed that some respondents had poor quality of life (63.8%) and other respondents had a good quality of life (36.3%). Factors related to quality of life were the severity of COPD (p=0.028), comorbidity (p=0.001) and quality of sleep (p=0.005). A multivariate analysis showed that patients with comorbidity were at risk 2,716 times to have poor quality of life. Conclusions: The severity of COPD, comorbidity and quality of sleep were related to have poor quality of life. Patients with COPD should early diagnosis of severity and should change their lifestyle better so as not to aggravate the quality of life.